SOCIAL ENTREPRENEUER IN ORGANIZATIONAL CULTURE AND ORGANIZATIONAL EFFECTIVENESS IN SUSTAINABILITY OF SEKOLAH PETERNAKAN RAKYAT NGUDI REJEKI KEDIRI - Nurus Sabani; Anggraini Sukmawati; I Made Sumertajaya (Indonesian Journal of Business and Entrepreneurship (IJBE), 2020)
This study aimed to analyze the influence of social entrepreneurs, organizational culture, and organizational effectiveness for the sustainability of the Sekolah Peternakan Rakyat Ngudi Rejeki (SPR). The study population and sample were all members of the Sekolah Peternakan Rakyat Ngudi Rejeki, amounting to 31 SPR members. Interviews and questionnaires did the data collection, and the data was analyzed with the structural equation model - partial least square (SEM-PLS). The results showed that social entrepreneurs have a positive and significant effect on organizational culture, organizational effectiveness, and indirectly on organizational sustainability; organizational culture has a positive and significant effect on organizational effectiveness. Culture has not significantly or indirectly affected sustainability. Organizational effectiveness has not significant effect on organizational sustainability. Keywords: organizational culture, organizational effectiveness, organizational sustainability, Social entrepreneur, SPR